Analysis of the Taaruf Parade of the Quran Tilawati Selection and Hadis (STQH) National Indonesia - Laxmi; La Ode Aris; Nirmalasari; Abdul Rahman; Muh Ikhlasul Amal (Institut Bahri Asyiq Galis Bangkalan, 2026)
The Quran Recitation and Hadith Competition (STQH) is a national event that combines religious aspects with local wisdom. Each region showcases its unique characteristics through traditional attire, cultural symbols, and distinctive ornaments. The objective of this study is to analyze and document the appearance of decorated vehicles and cultural representations from various provinces, as presented in the STQH Ta’aruf Parade. The research method employs qualitative descriptive analysis with an ethnographic approach. Data collection techniques include standard interviews, in-depth interviews, participant observation, and documentary analysis. The results of this study indicate that the Ta’aruf Parade in the 2025 National STQH serves as a medium for cultural representation that integrates religious values, local identity, and environmental awareness. Each contingent displays cultural symbols through decorated vehicles, traditional attire, and traditional arts that convey messages of social harmony and environmental conservation. Support from organizers and the government further strengthened the socio-economic impact by boosting local community activities. Art performances, including large-scale dances, demonstrated that cultural arts are utilized as a contextual means of religious outreach. The STQH functions not only as a venue for religious competition but also as a space for cultural preservation and the reinforcement of sustainable social values.